2007
DOI: 10.2353/ajpath.2007.070630
|View full text |Cite
|
Sign up to set email alerts
|

Expression Microarray Analysis Implicates Apoptosis and Interferon-Responsive Mechanisms in Susceptibility to Experimental Cerebral Malaria

Abstract: Specific local brain responses, influenced by parasite sequestration and host immune system activation, have been implicated in the development of cerebral malaria. This study assessed whole-brain transcriptional responses over the course of experimental cerebral malaria by comparing genetically resistant and susceptible inbred mouse strains infected with Plasmodium berghei ANKA. Computational methods were used to identify differential patterns of gene expression. Overall, genes that showed the most transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 71 publications
(51 reference statements)
3
65
0
Order By: Relevance
“…The expression microarray findings were again confirmed: CM-susceptible mice showed a higher number of terminal dUTP nick-end labeling-positive cells, primarily in the neurons of the cerebral cortex and cells of the leptomeninges. 4 The corroborative studies performed by Lovegrove and colleagues 4 add significantly to the data from initial microarray analysis and convincingly suggest a role for IFN-related processes and neuronal apoptosis in murine CM pathogenesis. Although other studies have suggested the importance of IFN, particularly IFN-␥, in murine CM, 19 only two very recent studies have documented neuronal apoptosis in murine CM.…”
Section: What Can Microarray Analysis Tell Us About Murine CM Pathogesupporting
confidence: 57%
See 3 more Smart Citations
“…The expression microarray findings were again confirmed: CM-susceptible mice showed a higher number of terminal dUTP nick-end labeling-positive cells, primarily in the neurons of the cerebral cortex and cells of the leptomeninges. 4 The corroborative studies performed by Lovegrove and colleagues 4 add significantly to the data from initial microarray analysis and convincingly suggest a role for IFN-related processes and neuronal apoptosis in murine CM pathogenesis. Although other studies have suggested the importance of IFN, particularly IFN-␥, in murine CM, 19 only two very recent studies have documented neuronal apoptosis in murine CM.…”
Section: What Can Microarray Analysis Tell Us About Murine CM Pathogesupporting
confidence: 57%
“…18 The methods of microarray analysis are as important as the microarray testing itself: appropriate and rigorous statistical analysis is key to accurate interpretation of results, and the methods and presentation of data analysis can make a big difference in communicating the main findings from within the many. In this regard, the inclusion of a gene-gene interaction network to create an "interactome" that identified hubs of interconnectivity is a major strength of the study by Lovegrove and colleagues, 4 allowing them to identify factors that appear to be particularly important in directing the overall transcriptional response to PbA infection. The finding that expression of several genes involved in regulation of IFN were up-regulated in CM-susceptible mice led to assessment of brain tissue by quantitative real-time reverse transcriptase (RT)-PCR directed at a number of immune-related genes.…”
Section: What Can Microarray Analysis Tell Us About Murine CM Pathogementioning
confidence: 99%
See 2 more Smart Citations
“…These apoptotic adjustments may also reflect the host's attempt to reduce immunopathology associated with unwanted activity of effector leukocytes and return to a status of cell/tissue homeostasis. An overcompensated host immune response which includes elevated apoptotic transcriptomic signals has been implicated in the immunopathology associated with infection with the malarial parasite Plasmodium falciparum (Lovegrove et al, 2007).…”
Section: Discussionmentioning
confidence: 99%